Cytotoxic and genotoxic effects of Solanum lycocarpum St.-Hil (Solanaceae) on the cell cycle of Lactuca sativa and Allium cepa - Chiavegatto, Raquel Bezerra; Chaves, Ana Luisa Arantes; Silva, Izabela Caputo Assis; Lima, Luciana Alves Rodrigues dos Santos; Techio, Vânia Helena (Acta Scientiarum. Biological Sciences, 2017)
Solanum lycocarpum St.-Hil popularly known as ‘fruta-de-lobo’ or ‘lobeira’ is native to the Brazilian Cerrado, and used in folk medicine due to its phytotherapic properties. The action of S. lycocarpum on the cell cycle and chromosomes in order to demonstrate whether there are aneugenic and/or clastogenic effects is unknown. Thus, this study aimed at investigating the cytotoxic and genotoxic potential of methanol and hexane extracts of S. lycocarpum on growth and cell cycle of Lactuca sativa and Allium cepa. Roots from both species were exposed for 72 hours to methanol and hexane extracts with 50, 100, and 200 µg mL-1 of S. lycocarpum. Slides were prepared by the squash technique and then analyzed to determine the mitotic index and the total of chromosomal and nuclear abnormalities. The frequencies of chromosomal and nuclear abnormalities were high and significant with a dose-dependent effect, indicating that S. lycocarpum has a cytotoxic and genotoxic action depending on the dose used on meristem cells of A. cepa and L. sativa.